Removal of chrome dye from carpet effluents using coal ‐ ii (rate processes) - Gupta G.S.; Prasad G.; Singh V.N. (My University, 2025)
The rate kinetics of adsorption of Omega Chrome Red ME (Mordant Red 19), a popular chrome dye often used in carpet industries, on coal has been studied. The kinetics of dye removal indicates the process to be diffusion controlled. A generalised empirical model is proposed for the kinetics at different initial concentrations. Correlations between intraparticle diffusion rate constant and initial concentration of dye and particle size of coal have been developed. Adsorbate film thickness at the surface of adsorbent is found to decrease with the rise of concentration, temperature of dye solution and coal particle size. The reduction in film thickness at higher temperature is indicative of the exothermic nature of the process, which was confirmed by the yield of negative heat of adsorption. © 1988 Taylor & Francis Group, LLC.